2004
DOI: 10.1007/s11664-004-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance-voltage characterization of pulsed plasma polymerized allylamine dielectrics for flexible polymeric field effect transistors

Abstract: Polyallylamine films, deposited on Si wafers by radio frequency (RF) pulsed plasma polymerization (PPP), were employed as insulating layers of metalinsulator-semiconductor (MIS) capacitors. The insulating polymer films were deposited at plasma reactor temperatures of 25°C and 100°C. Multiple frequency capacitance-voltage (C-V) measurements indicated that an in-situ heat treatment during film deposition increased the insulator dielectric constant. The dielectric constant, calculated from the C-V data, rose from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…[18,19] In this experiment, it is confirmed that a significant number of -COO À and -NH 3 þ polar entities, generated from the interaction of the polyvinylacetic acid and the polyallyl amine films, is present in the layered polymer films as shown by XPS and ATR FT-IR analysis. The k values, in the range of 5.7-6.2 at 1 MHz obtained without any post-deposition annealing, are relatively high for purely organic films containing only oxygen and nitrogen as heteroatoms.…”
Section: à2supporting
confidence: 66%
See 1 more Smart Citation
“…[18,19] In this experiment, it is confirmed that a significant number of -COO À and -NH 3 þ polar entities, generated from the interaction of the polyvinylacetic acid and the polyallyl amine films, is present in the layered polymer films as shown by XPS and ATR FT-IR analysis. The k values, in the range of 5.7-6.2 at 1 MHz obtained without any post-deposition annealing, are relatively high for purely organic films containing only oxygen and nitrogen as heteroatoms.…”
Section: à2supporting
confidence: 66%
“…It should be noted that all the devices in this study were measured without any post-deposition annealing. [18] The inset of Figure 6 shows the hysteresis behavior of the J-V characteristics for a 10-layer stack of polymer films. Some hysteresis is observed in alternating forward and backward voltage sweeps.…”
Section: à2mentioning
confidence: 99%
“…The use of organic thin films is an attractive way of immobilizing molecules and achieving superhydrophobic and dielectric coatings . Organic thin films can be directly deposited on almost any substrate by using a plasma‐assisted polymerization process .…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al . reported that polyallylamine films, deposited on Si wafers by radio frequency pulsed plasma polymerization, were employed as insulating layers of metal‐insulator‐semiconductor capacitors.…”
Section: Introductionmentioning
confidence: 99%